DESKRIPSI RENCANA PELAKSANAAN PEMBELAJARAN TEMATIK KURIKULUM 2013 KELAS II SDN 05 PONTIANAK SELATAN - Nurlisha Firmandia; Nurlisha Firmandia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study generally aims to describe the implementation plan for class II thematic learning at SD Negeri 05 Pontianak Selatan. This study used a qualitative approach with a descriptive research method. Participants in this study acted as data sources, namely class II teachers. The research instrument is a human instrument, namely researchers. Data collection techniques used are interviews, documentation studies. The data analysis technique used is the Miles and Hurberman model which includes four stages, namely data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that (1) the teacher has prepared thematic learning quite well, namely preparing a Learning Implementation Plan (RPP), preparing Learning Materials, preparing Learning Methods to be used, determining the type of Learning Media, participating in good learning trainings held by the government and non-government in the form of online training and webinars, then (2) Obstacles experienced by teachers in the learning process such as internet networks, students not focusing during the learning process, then (3) Solutions for teachers to overcome competency limitations by participating in various training or training, seminars or meetings carried out in one school cluster such as the Teacher Working Group (KKG).